Real‐time pricing response attack in smart grid. Issue 12 (24th March 2022) - Liu, Yang; Tian, Jue; Yuan, Xiaoshu; Ye, Binger; Sang, Zi; Yao, Xiangzhen; Li, Lin; Liu, Ting
Abstract: Real‐time pricing is an attractive tariff for demand response programs, in which consumers could provide load flexibility by adjusting their electricity consumption in response to time‐varying electricity prices. This paper reveals a new threat called real‐time pricing response attack (RPRA), which manipulates consumers' electricity consumption by tampering with electricity price signals. Simulations are performed in IEEE 24‐bus, 39‐bus, and 118‐bus systems, and the results show that 8% to 28% of the transmission lines could be overloaded by the attack, which could cause serious security problems. Results of sensitivity analysis indicate that the attack effects are influenced by various factors, such as DR models, price elasticity, line capacities etc. To defend against the RPRA attack, we have proposed various detection and mitigation strategies.